A Bi-level gaming programming for regional integrated energy system considering the users' reliability incentive. (January 2023) - Chen, Biyun; Chen, Yanni; Zhou, Hengwang; Bai, Xiaoqing; Li, Bin; Guo, Xiaoxuan
Highlights: User reliability incentive is proposed to realize reliability service differentiation. A master-followers bi-level model is proposed for decision making of operator and users. Reliability constraint is adjusted considering building thermal inertia and user's status. The consumptive ability for renewable energy would also be promoted. The utility in a society-wide is maximized with limited reliability resources. Abstract: In the context of the regional integrated energy system, as renewable energy increases and energy coupling gets higher, the operator has more resilience and flexibility to support reliability auxiliary service. To address energy reliability resource allocation, a novel method that user reliability incentive mechanism considering user reliability demand is proposed to help optimal decision making in a market vision. Thus, users' demand for reliability differentiation in time and space dimensions will become prominent. Accordingly, we propose a master-followers bi-level gaming model with a reliability incentive mechanism. The reliability model is also innovated in the reliability constraint; the reliability reserve margin is adjusted in real-time considering the building thermal inertia and user's status. Considering user's reliability incentive, operator dispatches economically in the upper level and obtain the reliability index. With reliability improvement delivered by the upper level, users chase their maximum energy benefits by adjusting load responds on HVAC. This is considered by building thermal inertia and formulate reliability incentives based on improvement. A case study verifies the superiority of the proposed model on the participant's economy, users' reliability, the renewable energy accommodation capacity, and differential reliability pricing. The sensitivity for external energy price and renewable energy permeability are also analyzed.